Radiological health risk assessment of water samples from Lake Albert, Hoima, Uganda - Afam Uzorka; Mundu Muhamad Mustafa; Tukahirwa Ivan; Saphina Biira; Oluwole Akiyode; Musa Bawa; Living Ounyesiga (Next Research, 2026)

Spatiotemporal Distribution of Cyanobacteria in Tropical Freshwater Reservoir and Machine Learning Prediction using Explainable Artificial Intelligence - Muhammad Sarfraz Ahmad Mangat; Teh Sabariah binti Abd Manan; Sharifah Sakinah Syed Abd Mutalib; Zarimah Mohd Hanafiah; Nur Azwa Muhamad Bashar; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala’in; Adel Gohari; Wan Hanna Melini Wan Mohtar; Muhammad Raza Ul Mustafa; et al. (Water, Air, & Soil Pollution, 2026)

Reconstructing acid sulfate soil ponds for conservation-oriented silvo-aquaculture: hydrological and soil controls on early mangrove establishment - Akhmad Mustafa; Asda Laining; Hidayat Suryanto Suwoyo; Hiroshi Imae; Toshifumi Serizawa; Rachman Syah; Mohammad Syaichudin; Makmur .; Agus Nawang; Ince Ayu Khairana Kadriah; Sri Redjeki Hesti Mulyaningrum; Lideman .; et al. (Journal of Coastal Conservation, 2026)

Prevalence and mechanisms of antimicrobial resistance in respiratory bacterial pathogens of ruminants: a systematic review - Sophia Peter; Muhammad Zaki Zulkiffle; Bura Paul Thlama; Muhamad Hakim Mohd Ali Hanafiah; Faez Firdaus Jesse Abdullah; Juriah Kamaludeen; Suhaili Mustafa (Veterinary Research Communications, 2026)

Innovative photothermal membrane distillation: Mitigating temperature polarisation with rice husk biochar - Chia Ming Liew; Mohd Hafiz Puteh; Mohd Hafiz Dzarfan Othman; Roziana Kamaludin; Siti Maryam Jasman; Parvin Asogan; Rendy Muhamad Iqbal; Mustapha Salisu Muhammad; Huda Nurul; Nor Ain Abu Samah; Jerry Heng; Huda Abdullah; et al. (Journal of Environmental Chemical Engineering, 2025)

Bibliometric mapping on the probiotic trends in managing aquaculture pathogens - Muhamad Firdaus Syahmi Sam-on; Shuhaimi Mustafa; Amalia Mohd Hashim; Wan Aida Wan Mustapha; Mohd Termizi Yusof; Nurul Aqilah Mohd Zaini; Mohamed Yusuf Mohamed Nazir (Food Bioscience, 2025)

Performance and land characteristics of brackishwater pond to support sustainability of Pacific white shrimp (Litopenaeus vannamei) culture intensive technology - Akhmad Mustafa; Rachman Syah; Tarunamulia; Mudian Paena; Wasir Samad; Erna Ratnawati; Admi Athirah; Ruzkiah Asaf; Akmal; Kamariah; Zylshal; Sarip Hidayat; et al. (Environmental Science and Pollution Research, 2024)

Cleaner and sustainable synthesis of high-quality monoglycerides by use of enzyme technologies: techno-economic and environmental study for monolaurin - Ahmad Mustafa; Sara Fathy; Ozben Kutlu; Fumiya Niikura; Abrar Inayat; Muhamad Mustafa; Tamer M. M. Abdellatief; Awais Bokhari; Olusegun David Samuel; Carlo Pastore; Luigi di Bitonto; M. A. Tawfik; et al. (Clean Technologies and Environmental Policy, 2023)
Currently, monoglycerides (MG) are produced using a complicated energy-intensive technology that contributes negatively toward greenhouse gas mitigation. This work suggests a cleaner and simpler one-step enzymatic production of α -monolaurin in an inert membrane reactor, where the reaction and enzyme separation are conducted simultaneously in one unit. Candida antarctica lipase (Lipozyme 435) was used to catalyze the esterification reaction between lauric acid and glycerin in a solvent-free system under mild temperatures. Response surface methodology was used to optimize the reaction conditions. The optimal conditions were a molecular sieve of 14.85% w/w, a temperature of 56.95 °C, an enzyme amount of 5.38% w/w, and a molar ratio of 4.75% w/w. The gas chromatography (GC) analysis showed that the α-monolaurin percentage was 49.5% when the enzymatic process (ENZ) was used. The conventional chemical (CHEM) and autocatalytic (AUT) esterification methods were also performed to study their proportional MG yields. The GC results showed the MG percentages of 43.9 and 41.7% for CHEM and AUT, respectively. Economic analysis was also conducted for the suggested enzymatic technique, and the findings were compared with those of the CHEM and AUT technologies. Using a plant capacity of 4950 t/year and 11% interest for the proposed ENZ process, the total capital investment of α-monolaurin production was preferably four times less than that of the CHEM process and three times less than that of the AUT method, presenting investment possibilities. However, the ENZ process showed the least profitability (net profit per day) among the three processes. Nevertheless, the return on investment and net present value for the ENZ process were preferably higher than those of CHEM and AUT because of its interestingly lower inside battery limit plant cost and less energy consumption. The AUT/CHEM processes generated a total carbon dioxide (CO 2 ) exhaust of 678.7 t CO 2 eq./year. In contrast, the ENZ process exhausted a total CO 2 of only 50 t CO 2 eq./year. The present integrated techno-economic and environmental study of α-monolaurin production emphasizes the green and cost benefits of the proposed ENZ technology. Graphical Abstract

Determination of prebiotic utilisation capability of potential probiotic Bacillus velezensis FS26 through in silico and in vitro approaches - Muhamad Firdaus Syahmi Sam-on; Shuhaimi Mustafa; Amalia Mohd Hashim; Mohd Termizi Yusof; Shahrizim Zulkifly; Muhamad Akhmal Hakim Roslan (Food Bioscience, 2023)

Association between dietary 3-monochloropropane-1,2-diol esters (3-MCPDE) and renal cancer in Peninsular Malaysia: exposure assessment and matched case-control study - Siti Hajar Muhamad Rosli; Mei Siu Lau; Tasnim Khalid; Siti Khuzaimah Maarof; Suganthi Jeyabalan; Syazwani Sirdar Ali; Norhayati Mustafa Khalid; Mohd Fairulnizal Md Noh; Ruhaya Salleh; Lalitha Palaniveloo; Mohamad Hasnan Ahmad; Nurul Izzah Ahmad; et al. (Food Additives & Contaminants: Part A, 2023)

Numerical modelling of wind flow for solar power generation in a case study of the tropical zones - Muhamad Mustafa Mundu; Stephen Ndubuisi Nnamchi; Kelechi John Ukagwu; Benjamin Aina Peter; Onyinyechi Adanma Nnamchi; Jotham Ivan Ssempewo (Modeling Earth Systems and Environment, 2022)

Natural metabolites from the soft coral Nephthea sp. as potential SARS-CoV-2 main protease inhibitors - Omnia Hesham Abdelhafez; John Refaat Fahim; Muhamad Mustafa; Asmaa M. AboulMagd; Samar Yehia Desoukey; Alaa M. Hayallah; Mohamed Salah Kamel; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

Differential modelling and simulation of solar power potential: a helio-application of biharmonic model - Stephen Ndubuisi Nnamchi; Muhamad Mustafa Mundu; Onyinyechi Adanma Nnamchi; Uche Onochie; Zaid Oluwadurotimi Jagun (Modeling Earth Systems and Environment, 2022)

Bioactive chemical constituents from Curcuma caesia Roxb. rhizomes and inhibitory effect of curcuzederone on the migration of triple-negative breast cancer cell line MDA-MB-231 - Mohammad Al-Amin; Nagla Mustafa Eltayeb; Melati Khairuddean; Salizawati Muhamad Salhimi (Natural Product Research, 2021)

Involvement of TRPM2 Channel on Hypoxia-Induced Oxidative Injury, Inflammation, and Cell Death in Retinal Pigment Epithelial Cells: Modulator Action of Selenium Nanoparticles - Dilek Özkaya; Mustafa Nazıroğlu; László Vanyorek; Salina Muhamad (Biological Trace Element Research, 2021)

Catharanthus roseus L. extract downregulates the expression profile of motility-related genes in highly invasive human breast cancer cell line MDA-MB-231 - Nagla Mustafa Eltayeb; Mohammad Al-Amin; Aiman Mohammed Yousif; Venugopal Balakrishnan; Salizawati Muhamad Salhimi (Biologia, 2021)

Aryl azide-sulfonamide hybrids induce cellular apoptosis: synthesis and preliminary screening of their cytotoxicity in human HCT116 and A549 cancer cell lines - Ahmed El-Kardocy; Muhamad Mustafa; Esam R. Ahmed; Samy Mohamady; Yaser A. Mostafa (Medicinal Chemistry Research, 2019)

Evaluation of distribution and sources of sewage molecular marker (LABs) in selected rivers and estuaries of Peninsular Malaysia - Sami M. Magam; Mohamad Pauzi Zakaria; Normala Halimoon; Ahmad Zaharin Aris; Narayanan Kannan; Najat Masood; Shuhaimi Mustafa; Sadeq Alkhadher; Mehrzad Keshavarzifard; Vahab Vaezzadeh; Muhamad S. A. Sani; Mohd Talib Latif (Environmental Science and Pollution Research, 2016)